2000
DOI: 10.1037/0022-3514.79.5.837
|View full text |Cite
|
Sign up to set email alerts
|

The looming maladaptive style: Anxiety, danger, and schematic processing.

Abstract: The importance of cognitive styles as psychological antecedents of psychopathology has gained increasing acceptance over the past 2 decades. Although ample research has explored cognitive styles that confer vulnerability to depression, cognitive styles that confer vulnerability to anxiety have received considerably less attention. In the present investigation, we examined the looming maladaptive style (LMS) as a cognitive style that functions as a danger schema to produce specific vulnerability to anxiety, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
161
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(171 citation statements)
references
References 49 publications
(100 reference statements)
7
161
0
3
Order By: Relevance
“…Perhaps more importantly, studies have also shown that LMS predicts subsequent change in symptoms of anxiety. In an undergraduate sample selected for low anxiety symptoms, LMS was found to predict change in symptoms of anxiety over a one week period (Riskind et al 2000). More recently, in an unselected undergraduate sample, Riskind et al (2007) showed that LMS significantly predicted change in symptoms of both OCD and worry and predicted change in symptoms of social anxiety at a trend level over a one week period.…”
Section: Looming Maladaptive Stylementioning
confidence: 97%
“…Perhaps more importantly, studies have also shown that LMS predicts subsequent change in symptoms of anxiety. In an undergraduate sample selected for low anxiety symptoms, LMS was found to predict change in symptoms of anxiety over a one week period (Riskind et al 2000). More recently, in an unselected undergraduate sample, Riskind et al (2007) showed that LMS significantly predicted change in symptoms of both OCD and worry and predicted change in symptoms of social anxiety at a trend level over a one week period.…”
Section: Looming Maladaptive Stylementioning
confidence: 97%
“…The measure consists of six brief vignettes of potentially threatening situations followed by eight questions, three of which assess the perception of increasing threat and constitute the looming maladaptive style subscale (Riskind et al, 2000). A variety of studies provide support for the validity of the scale, including its ability to predict worry and catastrophic thinking.…”
Section: Looming Maladaptive Style Questionnaire-revised (Lmsq-r)mentioning
confidence: 99%
“…BAT, kaygý ile oldukça yakýndan iliþkili olmasýna ve tüm kaygý bozukluklarýnda ortaya çýkan bir durum olmasýna karþýn, yapýlan çalýþmalar BAT'ýn kavramsal olarak kaygý ve endiþeden ayrýþacak biçimde anlamsaldan (semantik) ziyade görsel içeriðe sahip olduðunu göstermektedir (3,8). Ek olarak, kaygý ve depresyon arasýndaki yüksek korelasyonlara rað-men, yapýlan tüm araþtýrmalarda BAT, kaygý ile yüksek korelasyon gösterirken depresyonla iliþkisi oldukça sýnýrlý hatta bazý çalýþmalarda anlamlýlýk düzeyinin altýnda bulunmuþtur (3,9,10).…”
Section: Biliþsel Abartma Tarzý Modeliunclassified
“…Ek olarak, kaygý ve depresyon arasýndaki yüksek korelasyonlara rað-men, yapýlan tüm araþtýrmalarda BAT, kaygý ile yüksek korelasyon gösterirken depresyonla iliþkisi oldukça sýnýrlý hatta bazý çalýþmalarda anlamlýlýk düzeyinin altýnda bulunmuþtur (3,9,10). Buradan yola çýkarak, Riskind ve arkadaþlarý (3) BAT'ýn depresyonla iliþkisinin depresyon ve kaygý arasýn-daki örtüþmeden kaynaklandýðýný ileri sür-müþlerdir.…”
Section: Biliþsel Abartma Tarzý Modeliunclassified